Epidemiological and Clinical Characteristics of Cases During the Early Phase of COVID-19 Pandemic: A Systematic Review and Meta-Analysis - Koh, Jiayun; Shah, Shimoni Urvish; Chua, Pearleen Ee Yong; Gui, Hao; Pang, Junxiong (Frontiers in Medicine, 2020)
Background: On 29th December 2019, a cluster of cases displaying the symptoms of a "pneumonia of unknown cause" was identified in Wuhan, Hubei province of China. This systematic review and meta-analysis aims to review the epidemiological & clinical characteristics of COVID-19 cases in the early phase of the COVID-19 pandemic. Methods: The search strategy involved peer-reviewed studies published between 1st January and 11th February 2020 in Pubmed, Google scholar and China Knowledge Resource Integrated database. Publications identified were screened for their title & abstracts according to the eligibility criteria, and further shortlisted by full-text screening. Three independent reviewers extracted data from these studies, and studies were assessed for potential risk of bias. Studies comprising non-overlapping patient populations, were included for qualitative & quantitative synthesis of results. Pooled prevalence with 95% confidence intervals were calculated for patient characteristics. Results: A total of 29 publications were selected after full-text review. This comprised of 18 case reports, three case series & eight cross-sectional studies on patients admitted from mid-December of 2019 to early February of 2020. A total of 533 adult patients with pooled median age of 56 (95% CI: 49-57) and a pooled prevalence of male of 60% (95% CI: 52-68%) were admitted to hospital at a pooled median of seven days (95% CI: 7-7) post onset of symptoms. The most common symptoms at admission were fever, cough and fatigue, with a pooled prevalence of 90% (95% CI: 81-97%), 58% (95% CI:47-68%) & 50% (95% CI: 29-71%) respectively. Myalgia, shortness of breath, headache, diarrhea and sore throat were less common with pooled prevalence of 27% (95% CI: 20-36%), 25% (95% CI: 15-35%), 10% (95% CI: 7-13%), 8% (95% CI: 5-13%) and 7% (95% CI: 1-15%), respectively. ICU patients had a higher proportion of shortness of breath at presentation, as well as pre-existing hypertension, cardiovascular disease & COPD, compared to non-ICU patients in 2 studies (n= 179). Conclusion: This study highlights the key epidemiological and clinical features of COVID-19 cases during the early phase of the COVID-19 pandemic.